2012
DOI: 10.1111/j.1748-5827.2011.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal outbreaks in dogs associated with pantropic canine coronavirus in France and Belgium

Abstract: Infection with pantropic canine coronavirus was detected during outbreaks in France and Belgium. This was concurrent in most cases with canine parvovirus 2c. One outbreak was a deadly acute systemic disease with a single pantropic canine coronavirus infection. This is the first report of a fatality associated with pantropic canine coronavirus alone outside Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 13 publications
5
37
0
2
Order By: Relevance
“…The isolation of a new pantropic CCoV strain from a dead pup suggests that this variant is circulating in dogs, as described in recent investigations (Ntafis et al, 2012;Zicola et al, 2012), stressing the need to develop homologous vaccines on the basis of the poor crossprotection induced by enteric CCoV (Decaro et al, 2010a).…”
Section: Discussionmentioning
confidence: 92%
“…The isolation of a new pantropic CCoV strain from a dead pup suggests that this variant is circulating in dogs, as described in recent investigations (Ntafis et al, 2012;Zicola et al, 2012), stressing the need to develop homologous vaccines on the basis of the poor crossprotection induced by enteric CCoV (Decaro et al, 2010a).…”
Section: Discussionmentioning
confidence: 92%
“…As for CCoV, there is no agreement in the scientific community about the pathogenetic potential of this virus Gizzi et al, 2014;Schulz et al, 2008). Several studies have demonstrated the presence of CCoV in the faeces of dogs with diarrhoea in different countries, usually related to mild, self-limiting gastroenteritis (Decaro et al, 2005bStavisky et al, 2012;Cavalli et al, 2014;Costa et al, 2014;Licitra et al, 2014), although occasional detection of a hyper-virulent CCoV variant, referred to as pantropic CCoV, has been reported in severe, often fatal outbreaks Decaro et al, 2013;Ntafis et al, 2012;Zicola et al, 2012;Pinto et al, 2014). The role of CCoV as enteropathogen has been recently reconsidered by Duijvestijn et al (2016) that reported a strong association between diarrhoea and CCoV infection (p = 0.001) and results from our study also support this relation (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Puppies that were co-infected with CCoV and CPV showed severe clinical signs, which was in concordance with previous reports of frequently occurring co-infections with these pathogens (Decaro et al, 2011;Castro et al, 2013). CPV and CCoV synergize in their pathogenicity by interacting at the gut wall level (Zicola et al, 2012). Also CPV induces suppression of the immune system which facilitates superinfection with other pathogens (Castro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%